Contemporary changes in the area of glaciers in the western part of the Nordenskjold Land (Svalbard) - R. A. Chernov; A. Ya. Muraviev (Лëд и снег)
Climate warming in Svalbard, starting in the 1920s, caused a signifcant reduction in the mountain glaciation of the Nordenskjold Land. Te most extensive changes took place in the Western part of this territory due to the inﬂuence of the warm Spitsbergen current creating here the high temperature background. In addition, due to elevation of the level of the climatic snow line, many glaciers have actually lost the area of accumulation. From 1936 to 2017, the area of glaciers in the Western part of this region decreased by 169.5 km2 or 49.5%. Large valley glaciers and numerous small glaciers have lost the greatest area. Te relative losses of the area of glaciers were revealed to be proportional to sizes of them. In average over the past 80 years, glaciers with areas smaller 0.5 km² reduced by 76%, while big glaciers with areas larger 5 km2 – by only 34%. At present, there are 152 glaciers with a total area of 172.73±9.31 km2 in the Western territory of the Land of Nordenskjold (West of the Bolterdalen valley). According to the aerial photography of 2008–2009, the total area of glaciation of the Land of Nordenskjold covers 428 km2. High present-day rates of the retreating of local glaciers are apparently caused by extreme thinning of glacial tongues. At the same time, shrinking of glaciers located in the West of the Peninsula turned out to be more intensive than that of glaciers in its center. Although the Eastern territories receive less precipitation than glaciers near the coast of the Greenland Sea, the Eastern glaciers were found to be more resistant to reduction due to higher locations of them.